Optimizing quality of dental carving by preclinical dental students through anatomy theory reinforcement. Issue 4 (20th November 2017) - de Azevedo, Renato A.; Correa, Marcos B.; Torriani, Marcos A.; Lund, Rafael G.
Abstract : Knowledge of dental anatomy is of great importance in the practice of dentistry, especially in oral rehabilitation, because without this knowledge, professional practice is not possible. Dental carving plays a major role in training dental students as it develops their manual dexterity. This randomized controlled trial aimed to evaluate the influence of didactic‐theoretical reinforcement on the theoretical and practical knowledge of dental anatomy of preclinical students by examining the quality of the anatomical restorations performed by these students before and after a didactic‐theoretical reinforcement. For the evaluation of theoretical knowledge, a questionnaire with closed questions about dental anatomy was used. To evaluate the effect of didactic reinforcement on dental carvings, two groups of 15 preclinical students were assessed. Experimental group (G1) received a three‐hour theoretical tutoring on dental anatomy, while the control group (G2) did not. The dental carving scores obtained by the two different groups were compared using Student's t‐test. Cohen's d was used to estimate the effect sizes between groups. The frequency of correct answers given for each theoretical knowledge question was compared in each group using Fisher's exact test. T ‐test was also used to compare the means of the two groups' final scores of theoretical evaluations. To compare these final scores obtained in both carving and theoretical tests, a principal component analysis was performed with different items assessed in each test to obtain factor loading scores and a final weighted score, where factor loadings were considered for each item. Weighted scores were compared using t ‐test. Also, scores obtained during the head and neck course were assessed and compared using t ‐test. Spearman's correlation test was used to assess the correlation between scores obtained prior to the anatomy course and scores obtained in the dental carving exercise. The theoretical evaluation revealed no significant difference between the grades (mean ± SD) of G1 (85.1 ± 6.6%) and G2 (86.2 ± 9.1%) with the grades of a baseline test that was previously obtained when students submitted to the study ( P  = 0.725). Regarding the tooth carving assessment, the dental carving quality by students of G1 has significantly improved, except for tooth #23 ( P  = 0.096). Theoretical reinforcement of dental anatomy seems to improve the students' carving performance but does not enhance their knowledge about dental anatomy. Anat Sci Educ 11: 377–384. © 2017 American Association of Anatomists.